2018
DOI: 10.1016/j.eururo.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Prostate Cancer Patients with Germline DNA Repair Mutations: Retrospective Analysis from an International Study

Abstract: Patients with inherited DNA repair mutations benefit from standard therapies similarly to other metastatic prostate cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 17 publications
2
83
1
Order By: Relevance
“…We demonstrate that ctDNA can be applied to comprehensively profile AR and identify alterations in genes associated with DNA repair deficiency. Although these two biomarkers are considered promising for clinical decision making, recent data question the association between DNA-repair germline variants and response to PARP inhibitors [65] and the independent association between AR amplifications and response to abiraterone and enzalutamide treatment in mCRPC [55]. In the light of the controversy over AR-V7 [24], the only possible conclusion is the urgent need for efficient biomarker-driven clinical trials to identify in detail which patients may benefit from each therapy option.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that ctDNA can be applied to comprehensively profile AR and identify alterations in genes associated with DNA repair deficiency. Although these two biomarkers are considered promising for clinical decision making, recent data question the association between DNA-repair germline variants and response to PARP inhibitors [65] and the independent association between AR amplifications and response to abiraterone and enzalutamide treatment in mCRPC [55]. In the light of the controversy over AR-V7 [24], the only possible conclusion is the urgent need for efficient biomarker-driven clinical trials to identify in detail which patients may benefit from each therapy option.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, it should be noted that the response of patients with metastatic CRPC and homologous recombination repair gene mutations respond to standard therapies is similar to the response of patients without mutations. 226,227 The panel recommends clinical trial enrollment for men with prostate cancer and DNA repair gene mutations.…”
Section: Treatment Implications For Patients With Dna Repair Gene Mutmentioning
confidence: 99%
“…Germline mutations in BRCA2 are a well‐defined aspect of hereditary breast and ovarian cancer , but were underappreciated as a driver of hereditary prostate cancer as only 1–3% of unselected localized diagnoses harbour BRCA2 germline mutations . In the metastatic setting, however, germline BRCA2 mutations are common, with a prevalence of 3–6% (Table ); when combined with somatic mutations and homozygous deletions, up to 19% of metastatic CRPC (mCRPC) cases exhibit deleterious BRCA2 defects . The exact prevalence varies by patient ethnicity and geographic distribution; germline BRCA2 mutations were more common in a recent cohort of patients enriched for Ashkenazi Jewish ancestry (because of common founder mutations in that population) .…”
Section: High Prevalence Of Pathogenic Brca2 Mutationsmentioning
confidence: 99%
“…While both the Annala et al and Castro et al studies were prospective clinical trials, the numbers of patients with BRCA2 mutations were small and the patient populations (Canada, Spain, respectively) may not be generalizable to all other countries or healthcare systems. Indeed, a recent retrospective analysis of patients from the landmark publication by Pritchard et al in 2016 reported no significant difference in overall survival or PSA progression‐free survival (PFS) for patients with DDR germline mutations receiving AR signalling axis inhibitors (abiraterone or enzalutamide) . Additionally, data from Johns Hopkins reported that patients with CRPC carrying germline BRCA2 mutations ( n = 5), ATM mutations ( n = 3), and rare mutations in other DDR genes experienced a better outcome on AR axis inhibitors with regard to PFS and overall survival .…”
Section: Dna Damage Repair‐deficient Tumours Treated With Standard Ofmentioning
confidence: 99%